BUILDING A QUR'ANIC GENERATION: COMMUNITY SERVICE THROUGH TEACHING AND GUIDANCE OF CHILDREN AT AL-IKHLAS DAY SCHOOL IN KEBONDOWO VILLAGE - Abidin, Zaenal; Maulia Indana Zulfa; Khasanah, Uswatun (Jurnal Indonesia Mengabdi, 2025)
Community service activities through the Al-Ikhlas Qur’anic Learning Center (TPA) in Kebondowo Village have been ongoing since 1990, initiated by a local community leader, Mr. Rohmat, and are now continued by his descendants. The aim of this activity is to shape a Qur’anic generation through structured learning, starting from the basics (Iqro’) to advanced levels (Qur’an reading), memorization of short surahs, daily prayers, worship practices, and understanding the basic teachings of Islam. In addition, the routine weekly Yasinan (recitation of Surah Yasin) every Saturday night with children further strengthens spirituality and community bonding. The method involves direct guidance by TPA instructors with scheduled roles and activities. The results show a significant improvement in the children’s Islamic understanding and the growth of a religious culture in the local environment. During the month of Ramadan, activities become even more vibrant with group Qur’an recitation sessions. The conclusion of this community service initiative is that consistent TPA activities and Yasinan are a sustainable form of non-formal religious education that has a positive and meaningful impact on the community.